Association between changes in lean mass, muscle strength, endurance, and power following resistance or concurrent training with differing high protein diets in resistance-trained young males - Bagheri, Reza; Karimi, Zohreh; Camera, Donny M.; Scott, David; Bashirzad, Mahdi Ziaee; Sadeghi, Ramin; Kargarfard, Mehdi; Dutheil, Fred (Frontiers in Nutrition, 2024)
We assessed the relationship of changes in upper and lower body lean mass with muscle strength, endurance and power responses following two high protein diets (1.6 or 3.2 g . kg -1. d -1 ) during 16 weeks of either concurrent training (CT) or resistance training (RT) in resistance-trained young males.Methods: Forty-eight resistance-trained young males (age: 26 ± 6 yr, body mass index: 25.6 ± 2.9 kg.m -2 ) performed 16 weeks (four sessions•wk -1 ) of CT or RT with either 1.6 g . kg -1. d -1 protein (CT+1.6; n=12; RT+1.6; n=12) or 3.2 g . kg -1. d -1 protein (CT+3.2; n=12; RT+3.2; n=12). Relationships between upper (left arm + right arm + trunk lean mass) and lower body (left leg + right leg lean mass) lean mass changes with changes in muscle performance were assessed using Pearson's correlation coefficients.Results: For upper body, non-significant weak positive relationships were observed between change in upper body lean mass and change in pull-up (r=0.183, p=0.234), absolute chest press strength (r=0.159, p=0.302), chest press endurance (r=0.041, p=0.792), and relative chest press strength (r=0.097, p=0.529) while non-significant weak negative relationships were observed for changes in absolute upper body power (r=-0.236, p=0.123) and relative upper body power (r=-0.203, p=0.185). For lower body, non-significant weak positive relationships were observed between the change in lower body lean mass with change in vertical jump (r=0.145, p=0.346), absolute lower body power (r=0.109, p=0.480), absolute leg press strength (r=0.073, p=0.638), leg press endurance (r<0.001, p=0.998), relative leg press strength (r=0.089, p=0.564), and relative lower body power (r=0.150, p=0.332).Changes in muscle strength, endurance and power adaptation responses following 16 weeks of either CT or RT with different high protein intakes were not associated with changes in lean mass in resistance-trained young males. These findings indicate that muscle hypertrophy has a small, or negligible, contributory role in promoting functional adaptations with RT or CT, at least over a 16-week period.